2013
DOI: 10.1002/etc.2352
|View full text |Cite
|
Sign up to set email alerts
|

Predicted transport of pyrethroid insecticides from an urban landscape to surface water

Abstract: We developed a simple screening-level model of exposure of aquatic species to pyrethroid insecticides for the lower American River watershed (California, USA). The model incorporated both empirically derived washoff functions based on existing, small-scale precipitation simulations and empirical data on pyrethroid insecticide use and watershed properties for Sacramento County, California. We calibrated the model to in-stream monitoring data and used it to predict daily river pyrethroid concentration from 1995 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Pyrethroids are widely used neurotoxic insecticides frequently found in aquatic systems worldwide (Jorgenson et al, 2013) and shown to persist in sediments (Amweg et al, 2005;Weston et al, 2013). Pyrethroids are highly toxic to non-target organisms, including aquatic invertebrates and fish (Werner and Moran, 2008).…”
Section: Aop Case Study For Growth Impairment By Pyrethroidsmentioning
confidence: 99%
“…Pyrethroids are widely used neurotoxic insecticides frequently found in aquatic systems worldwide (Jorgenson et al, 2013) and shown to persist in sediments (Amweg et al, 2005;Weston et al, 2013). Pyrethroids are highly toxic to non-target organisms, including aquatic invertebrates and fish (Werner and Moran, 2008).…”
Section: Aop Case Study For Growth Impairment By Pyrethroidsmentioning
confidence: 99%
“…In the few studies to date, concentrations have commonly been detected in direct correlation with the local use patterns of agricultural and urban insecticides (Weston et al, 2009;Hladik and Kuivila, 2009;Weston and Lydy, 2010;Jorgenson et al, 2013). Estimates of loads and yields from watersheds are rare and relationships between differing land use patterns and individual pyrethroids are likely complex and confounded by the somewhat random availability of products and applicator trends at the local scale.…”
Section: Introductionmentioning
confidence: 96%
“…This increase in toxicity from the mixture further emphasizes the importance of testing mixtures especially because cyfluthrin and imidacloprid are found together in household insecticides, and it is likely that chemical mixtures leach into waterways and affect nontarget aquatic species (Jorgenson et al 2013). Furthermore, mixture testing is important to conduct for estimations of toxicity because organisms are seldom exposed to a single chemical stressor.…”
Section: Discussionmentioning
confidence: 97%
“…Several household and turf pesticides are available to consumers that include pyrethroid-neonicotinoid mixtures (Larson et al 2014); therefore, it is important to examine the effects of the two insecticides to nontarget species due to potential for the pesticide mixture to travel off-site into nearby urban streams (Jorgenson et al 2013). Several studies examined effects to nontarget species from cyfluthrin and imidacloprid individually, but none have evaluated the mixture.…”
mentioning
confidence: 99%